Antimicrobial susceptibility pattern for Salmonella Typhi isolated from blood in Shaheed Suhrawardy Medical College, Dhaka - Tarana, Mst Naznin; Shumu, Samshad Jahan; Khanam, Rashida Akter; Jahan, Hosne; Sarker, Soma; Bhowmic, Devolina; Sarwar, Sharmin (Journal of Shaheed Suhrawardy Medical College, 2019)
Background: Typhoid fever remains a public health concern in developing countries. Antibiotic therapy constitutes the mainstay of management and multidrug resistant Salmonella spp has been emerged as a major public health concern. Objective: This study was done to evaluate antimicrobial sensitivity pattern of Salmonella typhi isolated from blood in Shaheed Suhrawardy Medical College Hospital. Methods: The retrospective study was done from January 2017 to December 2017 at microbiology laboratory, Shaheed Suhrawardy Medical College. A total of 367 samples, 30 isolates of Salmonella typhi obtained from blood culture. Both the indoor and outdoor patients were enrolled in this study. Results: During one year study period, total 367 cases were enrolled and the prevalence of Salmonella typhi was 30 (8.2 %). Among them (56.1%) were male with a male to female ratio 1.27:1. The bulk (50.1%) cases were in the age group of 15-30 years, 14.4% cases were in less than 15 years and 6.5% cases were in more than 60 years of age. Regarding antibiotic sensitivity pattern, 70% strains were sensitive to amikacin, 73.33% to azithromycin, 63.33% to ceftazidime, 66.66% to ceftriaxone, 86.66% to ciprofloxacin and 70% were nalidixic acid resistant Salmonella typhi. Conclusion: Ciprofloxacin may be used to treat typhoid fever cases and Ceftriaxone, azithromycin may be used as alternative drugs if they are found susceptible in culture and sensitivity testing. J Shaheed Suhrawardy Med Coll, December 2018, Vol.10(2); 96-98